Entrepreneurship education: a case study in curriculum development - Smith, Gillian Gabrielle (My University, 2014)
This research report investigates some of the process and tensions involved in translating the perceived need for Entrepreneurship Education into the lived curriculum at selected schools in Gauteng, Advocates for Entrepreneurship Education from difierent sectors of society began to articulate this need in the mid-nineties urging schools to introduce Entrepreneurship Education programmes, and in some cases laying down how they believed it should be taught. A qualitative and exploratory research design was employed utilizing methods such as questionnaires, observations and interviews. The research carried out in this study identified the source of the original idea in the school, the reasons why teachers believed it was important to teach children entrepreneurship, the tensions and constraints encountered in doing so and the manner in which it is being presented. It also investigated the reasons why some of the schools in the sample have not introduced it One of the findings was that the status of the promoter had a direct bearing on the success of the course. Where it was the principal the course was most successful, where it was the media center teacher it was not initiated at all. Also, teachers indicated a variety of reasons for the importance of Entrepreneurship Education. The one quoted most often was the ne?d for the less able pupil to provide for his own employment and so by extension, the belief that to be a job-creator is less challenging than to be a job seeker. How the new course was slotted into the timetable by different schools was an indication of the tensions and constraints experienced. As a • utilitarian course with a practical component Entrepreneurship Education suffers the same low status as other subjects which are not tied into examinations. That schools had. not adopted Entrepreneurship Education was due either to ignorance or indifference in spite of efforts by advocates such as the state and subject interest groups.